A look up table design with 3D bipolar RRAMs - Chen, Yi-Chung (2013)
Look Up Table (LUT) is a basic configurable logic element in Field Programmable Gate Arrays (FPGAs). In a commercial product, Static Random Access Memory (SRAM) has been widely used in each LUT to store configured logic. Recently, emerging Resistive RAM (RRAM) has attracted a lot of attention for its high density and non-volatility. In this work, we explore a novel LUT design with bipolar RRAM devices. To obtain design efficiency, a 3D high-density interleaved memory structure is introduced in the proposed LUT. The corresponding peripheral circuits were developed with TSMC 0.18μm technology node. Compared to the traditional SRAM-based FPGA, the RRAM-based LUT demonstrates advantages such as a eliminating initialization stage, a much higher density with 56% area reduction, a bit-addressable write scheme, dynamic reconfiguration, and better flexibility in supporting various configurations.